Bimetallic Nanocatalysts Immobilized in Nanoporous Hydrogels for Long‐Term Robust Continuous Glucose Monitoring of Smart Contact Lens. Issue 18 (13th March 2022) - Kim, Su‐Kyoung; Lee, Geon‐Hui; Jeon, Cheonhoo; Han, Hye Hyeon; Kim, Seong‐Jong; Mok, Jee Won; Joo, Choun‐Ki; Shin, Sangbaie; Sim, Jae‐Yoon; Myung, David; Bao, Zhenan; Hahn, Sei Kwang
Abstract: Smart contact lenses for continuous glucose monitoring (CGM) have great potential for huge clinical impact. To date, their development has been limited by challenges in accurate detection of glucose without hysteresis for tear glucose monitoring to track the blood glucose levels. Here, long‐term robust CGM in diabetic rabbits is demonstrated by using bimetallic nanocatalysts immobilized in nanoporous hydrogels in smart contact lenses. After redox reaction of glucose oxidase, the nanocatalysts facilitate rapid decomposition of hydrogen peroxide and nanoparticle‐mediated charge transfer with drastically improved diffusion via rapid swelling of nanoporous hydrogels. The ocular glucose sensors result in high sensitivity, fast response time, low detection limit, low hysteresis, and rapid sensor warming‐up time. In diabetic rabbits, smart contact lens can detect tear glucose levels consistent with blood glucose levels measured by a glucometer and a CGM device, reflecting rapid concentration changes without hysteresis. The CGM in a human demonstrates the feasibility of smart contact lenses for further clinical applications. Abstract : Smart contact lenses containing bimetallic nanocatalysts immobilized in nanoporous hydrogels are developed for long‐term and robust continuous glucose monitoring. The smart contact lenses can accurately monitor increasing and decreasing blood glucose levels with 92.2% acceptable data in diabetic and normal rabbits. Finally, the clinical feasibility and safety of smart contact lenses are evaluated on the eyes of a human patient.